Experimental verification of P&O MPPT algorithm with direct control based on Fuzzy logic control using CUK converter - Radjai, T.; Gaubert, J.P.; Rahmani, L.; Mekhilef, Saad (Wiley, 2015)
The choice and design of a high efficient maximum power point tracking (MPPT) algorithm is a necessity in the PV system design. Many approaches have been proposed in literature, among them, the methods that are based on perturb and observe (P&O), widely used in commercial products due their simplicity and ease of implementation. In this paper, a new modified P&O (MPPT) method with adaptive duty cycle step size using fuzzy logic controller is proposed. Both, simulation and experimental design are provided in several aspects. The proposed and classical methods are developed and tested successfully using a CUKDC-DC converter, which is connected to a SunTech STP085B model. The proposed method is able to improve the dynamic response and steady-state performance of the PV systems simultaneously and effectively. In addition, analysis and comparison with the conventional fixed step size P&O have been presented. Copyright (C) 2015 John Wiley & Sons, Ltd.